Igelströmite, Fe3+(Sb3+Pb2+)O4, and manganoschafarzikite, Mn2+Sb3+2O4, two new members of the newly established minium group, from the Långban Mn–Fe deposit, Värmland, Sweden - D. Holtstam; J. Langhof; H. Friis; A. Karlsson; M. Erambert (European Journal of Mineralogy, 2024)
The two new minerals igelströmite, Fe3+(Sb3+Pb2+)O4, and manganoschafarzikite, Mn2+Sb<msubsup>23+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="12pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="a4d0982a5d283517da354ccda609a774"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-311-2024-ie00004.svg" width="12pt" height="17pt" src="ejm-36-311-2024-ie00004.png"/></svg:svg>O4, are found in the Långban Fe–Mn deposit, in open fractures in a fine-grained hematite ore, with minor amounts of aegirine, a serpentine-group mineral, fluorcalcioroméite, baryte, nadorite, mimetite and other late-stage minerals. Igelströmite is named after the Swedish geologist–mineralogist Lars Johan Igelström (1822–1897).